2022
DOI: 10.1101/2022.03.02.480688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flipped Over U: Structural Basis for dsRNA Cleavage by the SARS-CoV-2 Endoribonuclease

Abstract: Coronaviruses generate double-stranded (ds) RNA intermediates during viral replication that can activate host immune sensors. To evade activation of the host pattern recognition receptor MDA5, coronaviruses employ Nsp15, which is uridine-specific endoribonuclease. Nsp15 is proposed to associate with the coronavirus replication-transcription complex within double-membrane vesicles to cleave these dsRNA intermediates. How Nsp15 recognizes and processes dsRNA is poorly understood because previous structural studi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Finally, the recently published cryo-EM structure of NendoU bound to a 52 nt dsRNA provides support for a hypothesized RNA binding groove that spirals around the SARS-CoV-2 NendoU hexamer, interacting with both trimers. 13 , 18 This supports the hypothesis (depicted in Figure 9 ) that only one trimer can be active, especially in processing dsRNA, so that after product release the lower trimer is no longer able to perform substrate cleavage when substrate is bound to the top trimer molecules. This functional binding-change model would explain why (1) the hexamer is essential for the function, (2) only one trimer contains RNA in the cryo-EM structure, and (3) strong intrinsic differences were observed in flexibility between the two trimers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Finally, the recently published cryo-EM structure of NendoU bound to a 52 nt dsRNA provides support for a hypothesized RNA binding groove that spirals around the SARS-CoV-2 NendoU hexamer, interacting with both trimers. 13 , 18 This supports the hypothesis (depicted in Figure 9 ) that only one trimer can be active, especially in processing dsRNA, so that after product release the lower trimer is no longer able to perform substrate cleavage when substrate is bound to the top trimer molecules. This functional binding-change model would explain why (1) the hexamer is essential for the function, (2) only one trimer contains RNA in the cryo-EM structure, and (3) strong intrinsic differences were observed in flexibility between the two trimers.…”
Section: Discussionsupporting
confidence: 80%
“… 12 Supporting this hypothesis, NendoU was shown to cleave dsRNA in addition to ssRNA and cryoelectron microscopy (cryo-EM) analysis showed NendoU in complex with a 52 nt dsRNA. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of molecular mechanisms is also important; this led us to select N-terminal residue and active site residue mutations to further test the established roles of these amino acids [29, 35, 36, 42]. We recently determined a structure of Nsp15 bound to dsRNA [43]; of the Nsp15 mutants we characterized here, the only non-active site residues in the area of the dsRNA are D133 (~5 Å) and V128 (~9 Å).…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that as the Lpca approached the end of the dsRNA, its cleavage by nsp15 diminished (Figure S2C). Additionally, a previous structural study of the nsp15-dsRNA complex reported that dsRNA of approximately 35 bp was sufficient to interact across the nsp15 hexamer (Frazier et al, 2022). Hence, we hypothesized that an adequate length of dsRNA on both sides of the cleavage sites was necessary for binding to nsp15 and for localization of the cleavage sites into the active site of nsp15.…”
Section: Impact Of Dsrna Length On Cleavage By Sars-cov-2 Nsp15mentioning
confidence: 96%